2012
DOI: 10.1200/jco.2010.34.4010
|View full text |Cite
|
Sign up to set email alerts
|

Longer-Term Outcomes of Letrozole Versus Placebo After 5 Years of Tamoxifen in the NCIC CTG MA.17 Trial: Analyses Adjusting for Treatment Crossover

Abstract: Purpose The interim analysis of the National Cancer Institute of Canada Clinical Trials Group MA.17 trial showed that letrozole was significantly better than placebo in disease-free survival (DFS) for postmenopausal women with hormone receptor–positive breast cancer following about 5 years of tamoxifen therapy. When patients were unblinded, those on placebo were offered letrozole. Longer-term efficacy of letrozole, especially survival, was of particular interest because the median follow-up of the first interi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(73 citation statements)
references
References 13 publications
3
70
0
Order By: Relevance
“…In the MA-17 trial, postmenopausal women with hormone receptor-positive, early-stage breast cancer who had completed 4.5 to 6 years of adjuvant tamoxifen were randomized to extended therapy with letrozole or not. [68][69][70] With a median followup of 64 months, letrozole was associated with improved DFS (HR, 0.52; 95% CI, 0.45-0.61) and OS (HR, 0.61; 95% CI, 0.52-0.71) compared with placebo. 70 The ATLAS trial randomly allocated premenopausal and postmenopausal women to either 5 or 10 years (extended therapy) of tamoxifen.…”
Section: Adjuvant Endocrine Therapy Duration Of Adjuvant Endocrine Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MA-17 trial, postmenopausal women with hormone receptor-positive, early-stage breast cancer who had completed 4.5 to 6 years of adjuvant tamoxifen were randomized to extended therapy with letrozole or not. [68][69][70] With a median followup of 64 months, letrozole was associated with improved DFS (HR, 0.52; 95% CI, 0.45-0.61) and OS (HR, 0.61; 95% CI, 0.52-0.71) compared with placebo. 70 The ATLAS trial randomly allocated premenopausal and postmenopausal women to either 5 or 10 years (extended therapy) of tamoxifen.…”
Section: Adjuvant Endocrine Therapy Duration Of Adjuvant Endocrine Thmentioning
confidence: 99%
“…[68][69][70] With a median followup of 64 months, letrozole was associated with improved DFS (HR, 0.52; 95% CI, 0.45-0.61) and OS (HR, 0.61; 95% CI, 0.52-0.71) compared with placebo. 70 The ATLAS trial randomly allocated premenopausal and postmenopausal women to either 5 or 10 years (extended therapy) of tamoxifen. The outcome analyses of 6,846 women with ER-positive disease showed that by extending adjuvant treatment to 10 years, the risk of relapse and breast cancer-related mortality was reduced.…”
Section: Adjuvant Endocrine Therapy Duration Of Adjuvant Endocrine Thmentioning
confidence: 99%
“…Generally the therapy was well-tolerated, and the incidence of fracture was the same in each arm, suggesting that the risk of fracture seen in the above studies when compared to tamoxifen reflected the anti-osteopenic effects of tamoxifen (Goss et al, 2005(Goss et al, , 2008. When adjusted for cross-over that occurred after unblinding, there was also a significant improvement in overall survival observed in the entire population (HR 0.61, P < 0.001) (Jin et al, 2011) The EBCTCG has evaluated the use of aromatase inhibitors as compared to tamoxifen in a recent meta-analysis involving 19,000 patients. As was seen in the individual studies the use of an aromatase inhibitor whether upfront or sequentially with tamoxifen results in significantly reduced risk of recurrence, with absolute benefit of approximately 3%.…”
Section: Treatment Of Postmenopausal Women: Aromatase Inhibitorsmentioning
confidence: 64%
“…Although not definitive, the foregoing studies, together with the ma.17 trial [28][29][30][31][32][33][34][35][36] , suggest that hormonal treatment could be beneficial for some patients even after a delay of several years.…”
Section: 23mentioning
confidence: 99%
“…Supplementary Tables 3 and 4 present results from the ebctcg meta-analyses 40,41 , and Supplementary Table 5 presents results from the literature search [4][5][6][28][29][30][31][32][33][34][35][36] .…”
Section: 31mentioning
confidence: 99%